A Novel Algorithm for Defining the Mandibular Border. Issue 3 (23rd February 2022) - Rohrich, Rod J.; Agrawal, Nikhil A.; Avashia, Yash; Savetsky, Ira L.
Abstract : Summary: Techniques for defining the mandibular angle are a particular focus for patients around the world. Developing the desirable sharp contours is a combination of reducing bulkiness around the mandible while augmenting the border. Invasive techniques (e.g., face lifts and chin augmentation) can help define the mandible; however, younger patients are demanding more affordable and less invasive procedures. The "Nefertiti lift, " masseter neurotoxin, buccal fat excision, mandibular border augmentation with filler, and liposuction of the neck can all be done in the office and will produce excellent results. If the loss of definition is due to superior soft tissue, the next step is to determine if this is based on anterior or posterior soft-tissue excess. Posteriorly, it is caused by masseter hypertrophy, and anteriorly, it may be because of an enlarged or full buccal fat pad in the lower cheek area. If the loss of definition is inferior, the next step is to again define if it is anterior or posterior. Anterior excess tissue can be corrected with liposuction of the neck along with energy-based skin tightening technology. Posteriorly, the inferior pull of the platysma can be blunted with neurotoxin. Finally, once the soft tissues are adequate, the mandibular border can be augmented with filler. In this article, the authors propose an algorithm for when to utilize each of these procedures while reviewing proper technique.